Antioxidant, anti-tyrosinase, anti-aging potentials and safety of arabica coffee cherry extract - Kanokwan Kiattisin (2020)
© 2019, Chiang Mai University. All rights reserved. The coffee cherry (Coffea Arabica) is a by-product from the coffee production process that is widely used in agriculture; however, there are few reports regarding the application of coffee by-products in cosmetics. Therefore, this study aimed to investigate the antioxidant, anti-tyrosinase and anti-aging activities as well as the toxicity of coffee cherry extracts. The extracts of the coffee cherry fruits were obtained by fractionated extraction using hexane, ethyl acetate, and ethanol, respectively. Anti-aging bioactivities were investigated. Results showed that the ethyl acetate extract was shown to contain the highest total phenolic content (301.96 ± 4.05 mg GAE/g extract). It possessed good antioxidant activity according to the DPPH (IC50 value as 35.65 ± 1.35 µg/mL) and FRAP assays (FRAP value as 100.52 ± 0.08 mM FeSO4/g) that the results were higher than caffeine standard. The ethyl acetate extract also showed the highest anti-tyrosinase activity (IC50 values as 0.23 ± 0.01 mg/mL and 0.98 ± 0.02 mg/mL when used L-tyrosine and L-dopa as substrates) when compared with other extracts. However, it showed lower anti-tyrosinase activity than kojic acid and vitamin c. It also demonstrated the highest inhibition against matrix metallopeptidase-2 and hyaluronidase (% inhibition as 25.44 ± 2.1 and 92.95 ± 0.61) when compared with other extracts. Moreover, it was found to be non-toxic to NIH-3T3 cells according to the MTT assay with concentrations 8-800 µg/mL, and an irritation effect was not observed in HET-CAM assay (irritation score was 0.0, at the concentration of 10 mg/mL). Therefore, this coffee cherry extract could be an attractive natural extract for further development of whitening or anti-aging products. Moreover, this can be a way to develop the value of arabica coffee waste into a value product that can be applied in the cosmetics industry.